FROM SHIFTING CULTIVATION TO ECOLOGICAL RECOVERY: DETERMINING LAND AGE THROUGH TREE ABUNDANCE AND SOIL ANALYSIS IN MANOKWARI - Susanto, Slamet Arif (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
The shifting cultivation system is an integral part of the local culture of the Papuan people in Indonesia, persisting to this day. This study investigates the relationship between vegetation abundance and soil chemical composition in former plantation lands of varying ages in Papua, Indonesia. Three sites with distinct fallow periods - 5 years (BK-5), 10 years (BK-10), and 15 years (BK-15) - were analyzed. Multivariate analysis was employed to model the combination of dominant vegetation density and soil physical and chemical characteristics. The results revealed that the BK-5 site exhibited poor soil quality, characterized by acidic pH and low organic carbon and nitrogen content. In contrast, the BK-10 and BK-15 sites demonstrated improved soil fertility. The multivariate analysis highlighted distinct differences in vegetation composition and soil nutrient parameters among the sites, with specific plant species associated with particular soil conditions. The study confirms that older former plantation lands tend to have higher soil fertility, suggesting that short fallow periods may be insufficient for optimal soil fertility restoration. These findings underscore the importance of considering the age of former plantation lands and the role of vegetation in shaping soil conditions. This research provides valuable insights into the ecological recovery of post-agricultural landscapes in Papua.